Molodezh' Afganistana . Molodezh' Afganistana . Youth of Afghanistan . Молодежь Афганистана - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. The film is about the activities of youth organizations during the April Revolution, the consequences of the war in Afghanistan, and the Soviet role in the development of the country. Contributors: Shorokhov, V. (Director) Фильм о деятельности молодежных организаций во время Апрельской революции, последствиях войны в Афганистане и роли СССР в развитии страны. Создатели: Шорохов, В. (Режиссер)